The rule of law - Bingham, T. H. (London Allen Lane, 2010)
In this brilliant short book, Britain's former senior law lord, and one of the world's most acute legal minds, examines what the idea actually means. He makes clear that the rule of law is not an arid legal doctrine but is the foundation of a fair and just society, is a guarantee of responsible government, is an important contribution to economic growth and offers the best means yet devised for securing peace and co-operation. He briefly examines the historical origins of the rule, and then advances eight conditions which capture its essence as understood in western democracies today. He also discusses the strains imposed on the rule of law by the threat and experience of international terrorism.
Includes bibliographical references (p. 175-196) and index.
Keywords: Rule of law